Strategic Investor Behaviour and the Volume-Volatility Relation in Equity Markets - Randi Næs; Johannes A. Skjeltorp (Norges Bank, 2003)
We examine the volume-volatility relation using detailed data from a limit order driven equity market. Estimates of the intraday slope of the demand and supply schedules of the order book are found to capture regularities in spreads, trade size and submission strategies which are believed to be related to asymmetric information. On a daily level, the order book slope should also captures differences in dispersion of beliefs about stock values. The relationship between our daily slope measure and the contemporaneous volatility across companies and time supports models where strategic trading and dispersion of beliefs increase both volume and volatility.
hdl:11250/2498618
Keywords: G10; G20; 330; market microstructure; equity trading; asymmetric information